Studies on Swelling Behavior of HPMC based Matrix Tablets by the Application of Digital Imaging Technique - Dewan, Irwin; Elias-Al-Mamun, Md; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2009)
The widespread application of hydrogels in a number of applications like control of microfluidic flow, development of muscle-like actuators, filtration/separation and drug delivery makes it important to properly understand these materials. Understanding hydrogel properties is also important from the standpoint of their similarity to many biological tissues. The degree of swelling as well as the rate of swelling of the hydrogel was studied through experiments using digital photography. First of all the matrix was prepared by blending properly weighed HPMC, Theophylline and excipients in a laboratory mixture for 10 minutes followed by compression with 5 ton force for 30 seconds. The study was designed to evaluate the effect of hydrophobic materials on HPMC matrix tablets in terms of in vitro swelling study. Different viscosity grades of HPMC i.e. 6- cps, 15-cps and 50-cps were used to prepare tablets along with various hydrophobic materials. Among the hydrophobic materials stearic acid (SA), cetyl alcohol (CA), bees wax (BW), glyceryl monostearate (GMS), cetostearyl alcohol (CSA) and stearyl alcohol (STA) were used. It was found that presence of hydrophobic ingredients in the HPMC hydrogel matrix substantially reduces swelling of the matrix. In this work, the extent of swelling of HPMC matrix was evaluated by using digital photography and counting the pixels with Photoshop software. Finally, it was shown from the experiment that the rate and extent of drug release is mainly governed by swelling rate of different HPMC viscosity grade used and the nature of hydrophobic materials included into the matrix system. Key words: Swelling, Matrix, HPMC, Hydrogel, Photography. doi: 10.3329/dujps.v7i2.2174 Dhaka Univ. J. Pharm. Sci. 7(2): 169-175, 2008 (December)